2012
DOI: 10.1523/jneurosci.0737-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

Switch-Related and General Preparation Processes in Task-Switching: Evidence from Multivariate Pattern Classification of EEG Data

Abstract: The cued-trials task-switching paradigm is used to investigate the processes involved in preparation to change task. Task switch trials typically show poorer performance than task repeat trials, suggesting that additional or more time-consuming preparation processes are required to switch tasks. However, behavioral and neuroimaging studies have so far been unable to decipher whether preparing for a switch in task involves distinct cognitive processes to those required more generally on both switch and repeat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 24 publications
3
36
0
Order By: Relevance
“…Importantly, noninformative cues did not elicit either switch positivity. The early switch positivity temporally overlaps alpha band activity over the right VLPFC (IFG) (Mansfield, Karayanidis, & Cohen, 2012), a region strongly linked to inhibitory control (Aron & Poldrack, 2006; see also consistent right IFG activity evident in fMRI ALE meta-analysis, Figure 3), and is consistent with disengagement from the now irrelevant task set (Meiran, Hsieh, & Chang, 2011). In contrast, the late switch positivity is consistent with fMRI evidence that proactive control involves activation of task-specific cortical regions in anticipation of the upcoming target (Wylie, Javitt, & Foxe, 2006).…”
Section: The Nature Of Switch-specific Preparationsupporting
confidence: 74%
“…Importantly, noninformative cues did not elicit either switch positivity. The early switch positivity temporally overlaps alpha band activity over the right VLPFC (IFG) (Mansfield, Karayanidis, & Cohen, 2012), a region strongly linked to inhibitory control (Aron & Poldrack, 2006; see also consistent right IFG activity evident in fMRI ALE meta-analysis, Figure 3), and is consistent with disengagement from the now irrelevant task set (Meiran, Hsieh, & Chang, 2011). In contrast, the late switch positivity is consistent with fMRI evidence that proactive control involves activation of task-specific cortical regions in anticipation of the upcoming target (Wylie, Javitt, & Foxe, 2006).…”
Section: The Nature Of Switch-specific Preparationsupporting
confidence: 74%
“…The amplitude of this early switch-positivity is associated with both response time and response threshold -a measure of cautiousness in decision-making (Karayanidis et al, 2009). Using multivariate pattern classification analyses, Mansfield et al (2012) showed activity in a right frontal source for switch relative to non-switch trials within the same latency range (see also Lavric et al, 2008). These studies also showed later activation in parietal sources for trials that permit task-specific preparation, irrespective of whether the task switches or repeats (Lavric et al, 2008;Mansfield et al, 2012).…”
Section: Proactive Control and Theta Connectivitymentioning
confidence: 93%
“…Given neuroimaging evidence that preparation to switch and implementation of a switch response involve distinct networks (for review see Ruge et al, 2013), theta oscillatory synchronization for proactive and reactive control may be expected to involve distinct networks. Additionally, as previous work with this paradigm has shown increased alpha power when preparing to switch (Mansfield et al, 2012; see also Sauseng et al, 2006), we examine whether alpha oscillatory networks are also evident during switch preparation and/or implementation.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations